Endoscopic ultrasound assessment of lesions of the ampulla of Vater is of particular value in low‐grade dysplasia. Issue 1 (20th August 2012) - Roberts, Keith J.; McCulloch, Neil; Sutcliffe, Rob; Isaac, John; Muiesan, Paolo; Bramhall, Simon; Mirza, Darius; Marudanayagam, Ravi; Mahon, Brinder S.
Abstract Background: The accurate diagnosis of dysplasia or carcinoma within ampullary lesions can be difficult, but, when possible, identifies patients who require endoscopic or surgical resection, respectively. The role of endoscopic ultrasound (EUS) in diagnosing these lesions and the degree of dysplasia is unclear. Methods: Patients with lesions of the ampulla were identified over 5 years. Patients who did not undergo EUS were compared with those who did. Results: A total of 27 of 58 (47%) patients were investigated with EUS. Pretreatment diagnoses were correct in 93% of the EUS group vs. 78% of the no‐EUS group. Rates of diagnostic accuracy in low‐grade dysplasia (LGD), high‐grade dysplasia (HGD) and adenocarcinoma (ADC) were 72%, 20% and 96%, respectively, in the no‐EUS group, and 93%, 50% and 100%, respectively, in the EUS group. Every diagnosis of LGD in the EUS group was correct, whereas these diagnoses accounted for the majority of errors (eight of 13) in the no‐EUS group. High‐grade dysplasia was frequently misdiagnosed. More patients were treated by endoscopic resection in the EUS group (12 of 27 vs. five of 31; P= 0.025). Conclusions: Endoscopic ultrasound increases the accuracy of preoperative diagnosis of ampullary lesions and is particularly useful in patients with LGD because it permits safe endoscopic management. Patients with HGD must be reviewed carefully and considered for pancreatoduodenectomy.